Kompetensi Aparatur Pemerintah Desa Peley Kecamatan Totikum Selatan Kabupaten Banggai Kepulauan - Nurmala Nurmala; Rustam Tohopi; Yacob Noho Nani (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
The technical implementers of the rules and policies set out by the village chief are known as village officials. In order to properly and competently address community issues, they must have administrative abilities and public service ethics. Determining the motivations, traits, self-concept, knowledge, and abilities of the Peley Village government officials in South Totikum District, Banggai Kepulauan Regency, was the aim of this study. This study employed a descriptive qualitative methodology. The findings show that Peley Village government officials' level of competence is still below ideal. Officials' motivation is typically normative, their traits and self-concept do not fully support service professionalism, they still have a limited understanding of their responsibilities and rules, and they still have poor abilities, especially when it comes to using information technology. In order to increase the quality of public services and the efficiency of village government administration, this circumstance highlights the necessity for competency enhancement through ongoing training, coaching, mentoring, and performance evaluation. This study concludes that village officials' motivation, traits, self-concept, knowledge, and abilities are still subpar. To attain more efficient and professional village government performance, all of these elements must be enhanced.